Halal Certification Outreach to Optimize MSME Marketing in Rejosari Subdistrict, East Semarang District - H. M. Paramitayana; Lulus P. N. S. Surjanti; Universari, Nuria; D. I. Trilestari (Edusight Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aimed to enhance the understanding and participation of residents in Rejosari Subdistrict, East Semarang District, Semarang City, regarding the importance of obtaining halal certification. Halal certification serves as a quality assurance mechanism for partner products produced by micro, small, and medium enterprises (MSMEs). Limited information, insufficient coaching, and the perception that halal certification procedures are overly complex remain common barriers among MSME partners, including those in Rejosari. The program therefore focused on delivering knowledge and strengthening understanding of MSME halal certification to encourage participants to pursue certification and, in turn, improve marketing performance. The results indicate that participants developed greater awareness of the importance of halal certification and improved understanding of how to obtain it. Nevertheless, continued assistance and more technical training are required to help MSME actors navigate the halal certification application procedures more effectively.